Kajian Literatur: Aktivitas Antibakteri Ekstrak Herba Suruhan (Peperomia pellucida L.) - Ayu Rahmawatiani; Dewi Mayasari; Angga Cipta Narsa (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Suruhan (Peperomia Pellucida L.) is one of the weed plants that grow wild in humid environments. This plant is commonly found in Indonesia and has been used by the community as a medicinal plant. The secondary metabolites contained oh suruhan are saponins, phenols, flavonoids, and tannins. These compounds are thought to provide antibacterial activity. The purpose of writing this literature review is to determine the compound of secondary metabolites, the antibacterial activity of the extract, and the effective concentration as an antibacterial agent. The method used is literature review by searching journals database with the Google Scholar, PubMed, and Scient Direct. Based on the literature review, the secondary metabolites contained are flavonoids, tannins, steroids, phenols, saponins, glycosides, anterquinone, pellucidin A, stigmasterol, and fucosterol. The antibacterial activity test showed that the extract was able to inhibit gram-positive bacteria such as Bacillus subtilis, Propionibacterium acne, and Staphylococcus aureus, as well as gram-negative bacteria, such as Klebsiella pneumoniae, Shigella dysentriae, Pseudomonas aeruginosa, Pseudomonas fluoescens, Escherichia coli, and Salmonella typhi. The activity produced by gram-negative bacteria is more sensitive than gram-positive bacteria. While the effective concentrations of n-hexane extract against gram-positive and gram-negative bacteria were 10 mg/mL and 200 mg/L, the resulting inhibition zone diameters were 17.9 mm and 18 mm.